PENGEMBANGAN LKPD BERPOLA MODEL PROBLEM BASED LEARNING UNTUK PESERTA DIDIK KELAS VIII SMP - Puput Agus Sri (Jurnal Edukasi dan Penelitian Matematika, 2018)
One type of learning tool suggested by the goverment is Lembar Kerja Peserta Didik (LKPD). The proper use of LKPD helps leaner gain success learning outcomes. Base on the observations at SMPN 2 Padang that LKPD used by teacher is not provide a step that leads leaners to build understanding through real problems. The presentation of the material on the LKPD is patterned on direct formula. This is the underlying researcher for developing LKPD based PBL , so students are able to construct know leage through real problems. Data is collect through observation, questionnaires, interviews, and test problem solving abilities. The subjects of this research are students grade VIII SMP N 2 Padang. This research development is used Plomp made consists of phase preliminary research, prototype phase, and assessment phase. Based on these results, it can be concluded that the mathematics lesson equipment based on PBL which was conducted to student's of class VIII was valid, practical, and effective.Keywords – LKPD, PBL, Plomp